Respuesta :

Hi there!

[tex]\dfrac{x}{7}[/tex] = [tex]\dfrac{5}{3}[/tex]

[tex]3x = 35[/tex]

x = [tex]\dfrac{35}{3}[/tex]

Now, Substitute th' value of " x " in [tex]\dfrac{x + 7}{7}[/tex] :-


=> [tex]\dfrac{x}{7}[/tex] + [tex]\dfrac{7}{7}[/tex]

=> [tex]\dfrac{x}{7}[/tex] + 1

=> [tex] \dfrac{ \dfrac{35}{3} }{7} [/tex] + 1

=> [tex]\dfrac{35}{3}[/tex] × [tex]\dfrac{1}{7}[/tex] + 1

=> [tex]\dfrac{5}{3}[/tex] + 1

=> [tex]\dfrac{5 +3}{3}[/tex]

=> [tex]\dfrac{8}{3}[/tex]

Hence,
Th' required answer is obtained.

~ Hope it helps!
iCarl
[tex]\sf Hello![/tex]

[tex]\sf We're\: Given[/tex] :

[tex]\dfrac{\sf x}{\sf 7} = \dfrac{\sf 5}{\sf 3}[/tex]

⇒ [tex]\sf 3x = 35[/tex]

⇒ [tex]\sf x = \dfrac{\sf 35}{3}[/tex]

[tex]\sf Then,[/tex]

[tex]\dfrac{\sf x + 7}{\sf 7}[/tex]

⇒ [tex]\dfrac{\sf x}{\sf 7} + \dfrac{\sf 7}{\sf 7}[/tex]

⇒ [tex]\dfrac{\sf 35}{\sf 3} × \dfrac{\sf 1}{\sf 7} + 1[/tex]

⇒ [tex]\dfrac{\sf 5}{\sf 3} + 1[/tex]

⇒ [tex]\dfrac{\sf 5 + 3}{\sf 3}[/tex]

⇒ [tex]\dfrac{\sf 8}{\sf 3}[/tex]

[tex]\sf Therefore,[/tex]

[tex]\dfrac{\sf x + 7}{\sf 7}[/tex] = [tex]\dfrac{\sf 8}{\sf 3}[/tex]

~ [tex]\sf iCarl[/tex]